Pengaruh Intensitas Modal dan Konservatisme Akuntansi Terhadap Penghindaran Pajak - Muhamad Mashur Syawal; Azolla Degita Azis; Angga Prasetia (Komunitas Dosen Indonesia, 2024)
Tax is a very important component of state revenue. because 82.42% of total state revenue comes from taxes. One type of obstacle that hinders tax collection that causes state revenue to decrease is tax avoidance. This research aims to examine the influence of capital intensity and accounting conservatism on tax avoidance. Tax avoidance is measured using the Cash Effective Tax Rate (CETR). The approach used in this research is a quantitative method using secondary data obtained from financial reports published on the Indonesia Stock Exchange (BEI) website and company websites. The population in this study were Food and Beverages Sub-Sector companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2023 period. The sample used in this study included 15 companies obtained by purposive sampling method and SPSS software version 23 was used to analyze the data with a multiple linear regression analysis approach. The findings show that capital intensity has a significant negative effect on Tax Avoidance and accounting conservatism has a significant positive effect on tax avoidance. Large fixed asset storage is carried out by a company not solely to avoid taxes but rather it is done by the company with the aim of running the company's operations. The principle of conservatism applied in accelerating the recognition of costs or losses and delaying the recognition of income has an impact on reducing the profit used as the basis for calculating the company's tax obligations.